Institutional aspects of 'the curse of natural resources' - Mladen Anelković; Zoran Stefanović; Dragan Petrović (Economic Themes, 2024)
Natural resources are still a critically important input for society's productive capacity. Valorization of the importance of natural resources throughout the history of economic thought shows that their influence on economy is not monotonous and unambiguous. During the last few decades, the understanding of the 'curse of natural resources' has been exploited increasingly, as a challenge to the traditional view of their necessarily positive effect on the economy. The conservation of monolithic economic structures, with weak adaptive capacity, strongly dependent on the export of primary or lowprocessed products, in many countries with an abundance of natural resources, speaks in favor of this understanding. It is shown, however, that the nature and direction of the influence of natural resources on the quality of the economic structure and the sustainability of economic growth are closely related to the institutional structure of society. The nature of the effect of rent from natural resources on socio-economic flows - corruption, level of democracy, possible conflicts - is determined by the quality of institutions, while the relationship is also present in the reverse direction. In accordance with the abovementioned, the aim of the paper is to outline the main streams of thinking about this problem in economic theory. Particular attention is paid to the institutionalist approach, which links the effects of natural resources on relevant trends to the quality of social institutions. The construction and improvement of institutional solutions must be at the center of attention of the policy of the purposeful use of natural resources.
Keywords: B52; O43; P48; 330; natural resources; natural rent; institutions; corruption; economic development; democracy